Internal Auditor Performance: Audit Structure, Compensation, Recommendation Quality, OCB, and Role Conflict - Ida Zuraida; Betri; Muhammad Fahmi; Frizki Danu Rakhmat (The Indonesian Institute of Science and Technology Research, 2026)
Internal auditor performance plays a crucial role in strengthening corporate governance, internal control, and risk management within banking institutions. However, empirical evidence regarding the influence of audit structure, compensation, recommendation quality, OCB, and the moderating role of role conflict remains inconsistent. This study aims to examine the effects of audit structure, compensation, recommendation quality, and OCB on internal auditor performance, as well as the moderating effect of role conflict. A quantitative survey was conducted involving internal auditors from state-owned and regional-owned banks in Palembang City. Of the 117 distributed questionnaires, 58 valid responses were analyzed using multiple linear regression and MRA. The results indicate that audit structure, compensation, recommendation quality, and OCB simultaneously have a significant effect on internal auditor performance. Individually, OCB positively and significantly influences internal auditor performance, whereas audit structure and compensation show positive but insignificant effects, and recommendation quality has a negative but insignificant effect. Furthermore, role conflict does not significantly moderate the relationships between the independent variables and internal auditor performance. These findings highlight the importance of fostering extra-role behavior to enhance internal auditor performance beyond structural and financial aspects. The study contributes to the literature on internal auditing by providing empirical evidence from the Indonesian banking sector and offers practical implications for bank management in developing strategies to strengthen auditor performance through organizational support and OCB. Future studies are recommended to include broader samples and additional organizational and behavioral variables.